Do Early Childhood Schools Have Contextual Effect on Child Development Aged 3-6 Years in Tanjung Jabung Timur, Jambi? - Hardilla, Dinda Septiani; Salimo, Harsono; Pamungkasari, Eti Poncorini (Journal of Maternal and Child Health, 2020)
Background: